Improving Mental Health Knowledge for Adolescents: Literature Review: Peningkatan Pengetahuan Kesehatan Mental untuk Remaja: Tinjauan Pustaka - Nunung Wulandari; Apoina Kartini; Cahya Tri Purnami (Promotif : Jurnal Kesehatan Masyarakat, 2025)
Introduction: Mental health is a crucial human right, especially for adolescents. The WHO states that more than 50% of mental disorders appear by the age of 14, yet often go undetected, negatively impacting education and socialization. RISKESDAS 2013-2018 showed an increase in mental emotional disorders in 15 years old and above from 6.0% to 9.8%. Surveillance of child and adolescent mental health is critical, requiring awareness and resource allocation. Schools, as the closest environment, play a role in early detection of mental disorders and should increase knowledge about mental health to reduce stigma. This increased knowledge is essential for adolescents to overcome mental health problems and maintain a better quality of life. Methods: This study used a systematic literature review approach by following the PRISMA method. Data searches were conducted in October 2024 through various sources such as PubMed, Scopus, and Google Scholar, with the keywords “Mental Health Knowledge” and “Adolescent Mental Health”. So that a total of 20 articles were eligible for use in this study. Results: The 20 articles showed that interventions such as socialization and school health efforts significantly improved adolescents' knowledge about mental health. Conclusion: A significant increase in adolescents' knowledge related to mental health was made after the provision of interventions or treatments such as socialization, school health efforts and exposure related to mental health in adolescents. This is known based on the increase in scores on the adolescent post-test. KEYWORDS: Mental Health Knowledge; Adolescent Mental Health;